Correlation between pulp sensibility and magnetic resonance signal intensity following regenerative endodontic procedures in mature necrotic teeth- a retrospective cohort study - Noha Mohamed El-Kateb; Amr Mohamed Abdallah; Rania Noaman ElBackly (BMC, 2024)
Abstract Background With increasing studies being published on regenerative endodontic procedures (REPs) as a treatment modality for mature necrotic teeth, the assessment of outcomes following regenerative endodontic procedures has become more challenging and the demand for a better understanding of the regenerated tissues following this treatment is rising. The study aimed to correlate cold, electric pulp testing (EPT), and magnetic resonance imaging (MRI) signal intensity (SI) in mature necrotic teeth treated with regenerative endodontic procedures. Methodology This retrospective cohort study included eighteen adult patients who experienced tooth necrosis in mature maxillary anterior teeth recruited from the outpatient clinic, Conservative Dentistry Department, Faculty of Dentistry, Alexandria University, Alexandria, Egypt from July 2017 until December 2018 with 12 months of follow-up. regenerative endodontic procedures via blood clot were performed. The canals were instrumented by ProTaper Next (PTN) files until final sizes X3 or X5. Biodentine was used as cervical plug material. Pre and post-operative clinical follow-up was done where the patients' responses to cold and electric pulp testing were given a scoring system and were compared to the normal contralateral tooth. Pre and post-operative magnetic resonance imaging signal intensity of both the involved tooth and its contralateral at the middle and the apical thirds of the root canals were assessed after 3, 6, and 12 months. Data was analyzed using the ANOVA, Friedman and Bonferroni tests. Significance was set at a p-value < 0.05. Results All 18 teeth scored a baseline score of "2" for cold and electric pulp testing. There was a significant difference between scores of the cold test at baseline and 12-month follow-up (p < 0.001). There was a significant difference between scores of the electric pulp testing of baseline and 12-month follow-up (p < 0.001). There was a moderately significant indirect (inverse) correlation between magnetic resonance imaging signal intensity and cold test in both the middle and apical thirds at 12 months. No significant correlations were detected between magnetic resonance imaging signal intensity and electric pulp testingat any of the time intervals (p > 0.05). Conclusion Magnetic resonance imaging is a successful non-invasive method to assess outcomes of regenerative endodontic procedures and correlating it with another reliable method of assessing pulpal responses, cold test, could validate these outcomes. Clinical trial registration The study was registered with ClinicalTrials.gov (ID: NCT03804450).